Truly Distributed Optical Fiber Sensors for Structural Health Monitoring: From the Telecommunication Optical Fiber Drawling Tower to Water Leakage Detection in Dikes and Concrete Structure Strain Monitoring - Jean-Marie Henault; Gautier Moreau; Sylvain Blairon; Jean Salin; Jean-Robert Courivaud; Frédéric Taillade; Erick Merliot; Jean-Philippe Dubois; Johan Bertrand; Stéphane Buschaert; Stefan Mayer; Sylvie Delepine-Lesoille (Advances in Civil Engineering)
Although optical fiber sensors have been developed for 30 years, there is a gap between lab experiments and field applications. This article focuses on specific methods developed to evaluate the whole sensing chain, with an emphasis on (i) commercially-available optoelectronic instruments and (ii) sensing cable. A number of additional considerations for a successful pairing of these two must be taken into account for successful field applications. These considerations are further developed within this article and illustrated with practical applications of water leakage detection in dikes and concrete structures monitoring, making use of distributed temperature and strain sensing based on Rayleigh, Raman, and Brillouin scattering in optical fibers. They include an adequate choice of working wavelengths, dedicated localization processes, choices of connector type, and further include a useful selection of traditional reference sensors to be installed nearby the optical fiber sensors, as well as temperature compensation in case of strain sensing.